2019
DOI: 10.1002/admi.201900740
|View full text |Cite
|
Sign up to set email alerts
|

High Moisture Barrier with Synergistic Combination of SiOx and Polyelectrolyte Nanolayers

Abstract: The lifespan of most organic electronics, and many types of food, depend on the oxygen and moisture barrier of the packaging materials. Despite exhibiting excellent oxygen barrier and being relatively easy to produce, polyelectrolyte multilayer nanocoatings (PEM) show limited moisture barrier. SiO x thin films can exhibit good moisture barrier, but rigidity that leads to cracking is a Received: ((will be filled in by the editorial staff))Revised: ((will be filled in by the editorial staff))

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…By alternatively depositing oppositely charged materials conformal and ultra-thin coatings can be prepared by the Lbl-technology from aqueous environments (Li et al 2020, Richardson et al 2015. Lbl assembly is a nanocoating technology for gas barrier and gas separation coating (Qin et al 2019a, 2019b, Song et al 2018.…”
Section: Layer-by Layer Assembly To Improve Barrier Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By alternatively depositing oppositely charged materials conformal and ultra-thin coatings can be prepared by the Lbl-technology from aqueous environments (Li et al 2020, Richardson et al 2015. Lbl assembly is a nanocoating technology for gas barrier and gas separation coating (Qin et al 2019a, 2019b, Song et al 2018.…”
Section: Layer-by Layer Assembly To Improve Barrier Propertiesmentioning
confidence: 99%
“…There are, however, approaches that may alleviate this problem. Hence, it has been shown that SiO x sandwich between two PEM layers based on PEI and polyacrylic acid had a very high moisture resistance (Qin et al 2019b).…”
Section: Layer-by Layer Assembly To Improve Barrier Propertiesmentioning
confidence: 99%
“…Among the various methods developed for flexible encapsulation, multilayer hybrid coatings consisting of alternating inorganic and organic layers are a promising candidate. 7,8 Ultrathin inorganic layers, such as SiO 2 and Al 2 O 3 , serve as impermeable gas barrier, owing to their rigid compact crystalline structure; while thicker polymer layers fill the defects of the inorganic layers and provide flexibility. Multilayer hybrid coatings have been fabricated using a variety of methods.…”
Section: Introductionmentioning
confidence: 99%
“…We propose replacement of one of them for the weak polyelectrolyte to avoid rigidity. Additionally, the application of polymer free-standing film demands the incorporation of metal complexes and structures. , …”
Section: Introductionmentioning
confidence: 99%